Pengembangan Kamus Mini Kosakata Arab-Indonesia untuk Membantu Pembelajaran Bahasa Arab Kelas X Ma Plus Sunan Drajat 7 Gesikharjo Palang Tuban - Arif Widodo; Nurul Janah (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2022)
Learning is a process activity and is a very fundamental element in every level of education. Learning activities are the most basic and important activities in the whole educational process. In learning, there is interaction between teacher and students. Lack of student handbooks, lack of mufradat treasury, lack of confidence, and shyness are obstacles in learning Arabic. To help subject teachers improve understanding, vocabulary vocabulary, increase self-confidence, reduce shyness and present learning materials in an interesting way, it is necessary to have media, methods, and other tools such as books, dictionaries, magazines, and others. This study aims to develop a mini-dictionary of Arabic-Indonesian vocabulary to help learning Arabic and to support the ability to master vocabulary, as a reference and teacher guidance. The subjects of this study were students of class X MA Plus Sunan Drajat 7 Gesikharjo Palang Tuban. The type of research used is research and development (Research and Development) in which the author collaborates with Arabic language teachers, all components of the institutions that are used as research sites and all the lecturers of the Sunan Drajat Islamic Boarding School Lamongan.